Hepatic fascioliasis: report of a patient - Néstor E. Vega Alonso; Nieves del Carmen de la Barca Jiménez; Osbel Quintana Morales (Acta Médica del Centro, 2013)
It is reported the case of a patient with unexplained fever, abdominal pain, eosinophilia and hepatic nodular images observed in ultrasound and abdominal computed tomography, suggestive, initially, of poly-metastatic liver. Laparoscopic findings in the hepatic gland showed visceral larva migrans and later, by the technique of conical cup, Fasciola hepatica eggs appeared in feces. Triclabendazole treatment was decided in two doses; the therapeutic response was good.